Oxidative Stress and Vascular Damage in Hypertension: Role of Angiotensin II - Agostino Virdis; Emiliano Duranti; Stefano Taddei (International Journal of Hypertension, 2011)
Reactive oxygen species are oxygen derivates and play an active role in vascular biology. These compounds are generated within the vascular wall, at the level of endothelial and vascular smooth muscle cells, as well as by adventitial fibroblasts. In healthy conditions, ROS are produced in a controlled manner at low concentrations and function as signaling molecules regulating vascular contraction-relaxation and cell growth. Physiologically, the rate of ROS generation is counterbalanced by the rate of elimination. In hypertension, an enhanced ROS generation occurs, which is not counterbalanced by the endogenous antioxidant mechanisms, leading to a state of oxidative stress. In the present paper, major angiotensin II-induced vascular ROS generation within the vasculature, and relative sources, will be discussed. Recent development of signalling pathways whereby angiotensin II-driven vascular ROS induce and accelerate functional and structural vascular injury will be also considered.